The Intervening Sequence of Coxiella burnetii: Characterization and Evolution - Warrier, Indu; Walter, Mathias C.; Frangoulidis, Dimitrios; Raghavan, Rahul; Hicks, Linda D.; Minnick, Michael F. (Frontiers in Cellular and Infection Microbiology, 2016)
The intervening sequence (IVS) of Coxiella burnetii, the agent of Q fever, is a 428-nt selfish genetic element located in helix 45 of the precursor 23S rRNA. The IVS element, in turn, contains an ORF that encodes a hypothetical ribosomal S23 protein (S23p). Although S23p can be synthesized in vitro in the presence of an engineered E. coli promoter and ribosome binding site, results suggest that the protein is not synthesized in vivo. In spite of a high degree of IVS conservation among different strains of C. burnetii, the region immediately upstream of the S23p start codon is prone to change, and the S23p-encoding ORF is evidently undergoing reductive evolution. We determined that IVS excision from 23S rRNA was mediated by RNase III, and IVS RNA was rapidly degraded, thereafter. Levels of the resulting 23S rRNA fragments that flank the IVS, F1 (~1.2 kb) and F2 (~1.7 kb), were quantified over C. burnetii’s logarithmic growth phase (1-5d). Results showed that 23S F1 quantities were consistently higher than those of F2 and 16S rRNA. The disparity between levels of the two 23S rRNA fragments following excision of IVS is an interesting phenomenon of unknown significance. Based upon phylogenetic analyses, IVS was acquired through horizontal transfer after C. burnetii’s divergence from an ancestral bacterium and has been subsequently maintained by vertical transfer. The widespread occurrence, maintenance and conservation of the IVS in C. burnetii imply that it plays an adaptive role or has a neutral effect on fitness.